2015
DOI: 10.1038/srep09352
|View full text |Cite
|
Sign up to set email alerts
|

Revealing sub-μm and μm-scale textures in H2O ice at megabar pressures by time-domain Brillouin scattering

Abstract: The time-domain Brillouin scattering technique, also known as picosecond ultrasonic interferometry, allows monitoring of the propagation of coherent acoustic pulses, having lengths ranging from nanometres to fractions of a micrometre, in samples with dimension of less than a micrometre to tens of micrometres. In this study, we applied this technique to depth-profiling of a polycrystalline aggregate of ice compressed in a diamond anvil cell to megabar pressures. The method allowed examination of the characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 72 publications
2
57
0
Order By: Relevance
“…TDBS assisted by diffraction gratings could be also advantageous in several applications with limited optical access to the samples [12,40,47]. It could provide the opportunity to monitor multiple BS processes/frequencies even with incident and the detected/scattered light propagating collinearly (for example, in the case of the probe light incident normally on the grating and the detection of either reflected or transmitted light in the directions also normal to the grating surfaces).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TDBS assisted by diffraction gratings could be also advantageous in several applications with limited optical access to the samples [12,40,47]. It could provide the opportunity to monitor multiple BS processes/frequencies even with incident and the detected/scattered light propagating collinearly (for example, in the case of the probe light incident normally on the grating and the detection of either reflected or transmitted light in the directions also normal to the grating surfaces).…”
Section: Discussionmentioning
confidence: 99%
“…Picosecond acoustic interferometry (PAI) is a powerful opto-acousto-optic technique for nondestructive and noncontact testing of transparent materials at the nanoscale [1][2][3][4][5][6][7][8][9][10][11][12][13]. First, using an ultrashort pump laser pulse, a propagating picosecond coherent acoustic pulse (CAP) is launched into the material.…”
Section: Introductionmentioning
confidence: 99%
“…In this situation, well suited for the investigation of mechanical properties of ultrathin solid or liquid samples, the occurrence of time-domain Brillouin scattering (TDBS) phenomena in transparent materials has been used to investigate viscoelastic properties of matter at ultrasound GHz to THz frequencies [6]. Recently, several examples have shown that TDBS is sensitive to diverse phenomena, including spatial mechanical, optical or acousto-optical inhomogeneities [7][8][9][10][11][12][13], non-linear acoustic waves or weak shock waves [14,15], and even GHz transverse acoustic phonons in viscoelastic liquids [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Perfect reflection of the acoustic pulses from the mechanically free or rigid surfaces is accompanied, in general, only by an abrupt phase shift of the sinusoid [4][5][6]. The time at which the acoustic pulse arrives at the interface can be identified through the observation of the phase and/or amplitude changes of the initial sinusoid and/or through the appearance of an additional sinusoidal contribution to the transient reflectivity at a different Brillouin frequency [7][8][9][10][11][12][13][14][15]. The PAI is useful for the acoustic pulse time-of-flight measurements [9,14] and is commonly applied to derive velocities of the acoustic waves and thicknesses of thin films.…”
mentioning
confidence: 99%